An ecological examination of teacher emotions in an EFL context - Han, Yawen; Wei, Rining; Wang, Jing (Frontiers in Psychology, 2023)
Guided by a revised version of Cross and Hong’s (2012) framework based on Bronfenbrenner’s (1979) ecological system theory, the present study adopted a mixed-methods approach to explore teacher emotions in an EFL context. It aims to better understand teacher emotions and the influencing factors of these emotions in the microsystem, mesosystem, exosystem, and macrosystem of the above-mentioned framework. A total of 109 university EFL teachers completed an online questionnaire survey, and seven of them participated in the follow-up semi-structured interviews. The quantitative analysis of the questionnaire data revealed that the participants demonstrated different levels of the five focal emotions (joy, love, anger, fear, and sadness), and joy was the most frequently experienced emotion. Results also suggested that interactions with students, colleagues, leaders and family (from the microsystem), struggle with work-family balance (from the mesosystem), the performance evaluation system (from the exosystem) and the curriculum reform (from the macrosystem) emerged as important influencing factors of teacher emotions. Implications were also discussed, which provide suggestions for regulating emotions of EFL teachers in tertiary institutions within China and possibly beyond.